شروڤه‌كرن و چاره‌سه‌ریا شاشیێن خالبه‌ندیێ و رێنڤیسێ د زمانێ راگه‌هاندنێدا (رۆژناما ئه‌ڤرۆ وه‌ك نموونه)‌ - MOHAMMAD, SULAIMAN HISHYAR; RAJAB, SULAIMAN ISMAIL (Journal of Duhok University, 2020)
The lack of a unified dictation system among all classes of society today created a major problem for the Kurdish dictation system, especially in the field of education, and this problem appears more clearly in the form and technique of writing. The lack of a strong linguistic center to supervise this thing facilitated that each party, according to their personal information, change the form of writing and use it according to their desire, or that the language of the media often does not pay attention to the language and the laws of the language, and the goal is that their main purpose is to deliver the message to readers in a simple and fast manner. Therefore, the language side is neglected, even though the language of the media is a powerful tool for preserving and developing the language because in the easiest way, all parts of society can benefit from new words and terms provided that this language is free of grammatical and spelling errors. That is why this language must be analyzed academically and accurately, and acceptable and normative examples must be shown and become a basis for the development of the language. This research is an academic scientific attempt to determine the correct and scientific principles of a correct spelling system in terms of dictation and technique